No Broken Link : The Vulnerability of Telecommunication Infrastructure to Natural Hazards - Sandhu, Himmat Singh (World Bank, Washington, DC, 2019)
The global economy is increasingly digital. The internet and other information and communicationtechnologies (ICTs) are changing the way individuals, businesses and governments operate. Theirresilience to natural disasters, and their ability to recover in the aftermath, is thus critical to the resilience of the economy. This chapter discusses the impact of climate events on various types of digital infrastructure. It highlights key considerations for governments and digital infrastructure owners to make their infrastructure more resilient, while maintaining affordability of services. We find that digital infrastructure is vulnerable to various climate risks, but that technology choices and network design can improve redundancy and resilience of networks, by design. Certain infrastructures warrant greater ex ante investment in their resilience considering their criticality in the broadband value chain (submarine cables or landing stations) while others could follow repair and recovery options (mobile network antennas, poles, and towers). We conclude with recommendations for the public and private sectors, noting that governments and sectorregulators can improve network resilience, and increase coordination given the distributedownership and governance models in the industry.